Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T19:55:47+01:00
A) B(3,0), wektor AB[-1,1]
Wykorzystujemy wzór
AB=[x,y]=[x(B)-x(A), y(B)-y(A)] czyli
[-1,1]=[3-x(A),0-y(A)]
po współrzędnych
-1 =3-x(A)
-4=-x(A)
x(A)=4
y(A)=-1
zatem A=(4,-1)
b) B)2,5), wektor AB[0,2]
0=2-x(A)czyli x(A)=2
2=5-y(A)
2-5=-y(A)
y(A)=3
A=(2,3)

c) B(-1,-3), wektor AB[-2,-3]
-2=-1-x(A) , x(A)=1
-3=-3-y(A) , y(A)=0
A=(1,0)
d) B(-2/3, -1), wektor AB[5,-6]
5= -2/3-x(A)
-5 2/3=x(A)
-6=-1-y(A)
y(A)=5
A=(5 2/3 , 5)
e) B(12,15), wektor AB [-10,10]
-10=12-x(A)
x(A)=22
10=15-y(A)
y(A)=5
A=(22,5)
f) B(17,-13), wektor AB[17,-13]
17=17-x(A) , x(A)=0 i y(A)=0
A=(0,0)
3 5 3